Visible light communication using new Flip-FBMC modulation system technique - Abdullah Ali Qasim; Husam Noman Mohammed Ali; Ali Kadhim Obaid; M. F. L. Abdullah; R. Talib; M. S. M. Gismalla; Wafi A. Mabrouk (Universitas Ahmad Dahlan, 2021)
Filter bank multi-carrier (FBMC) modulation in the visible light communication (VLC) system is one of the most promising modulation systems in optical wireless communications (OWC), especially in 5G and 6G future applications. FBMC has a wide bandwidth compared to other modulation systems. One of the highest degree essential conditions for utilising the signal in VLC is that the signal is real positive, the signal is agreeable with intensity modulation/direct detection (IM/DD), where Hermitian symmetry (H.S) is utilised to get a real signal (RE) and to be unipolar direct current (DC)-bias is used. Here the challenge arises as this method increases complicating, due to the modulation of the N number of frequency symbols, these symbols need 2N inverse fast fourier transform (IFFT) and fast fourier transform (FFT), in addition to energy consumption. This research focused on the time domain and not the frequency domain by using the traditional complex FBMC generation signal, and to obtain the RE signal by placing the RE signal side by side with the imaginary signal (IMs) in a row, and then using new Flip-FBMC technology, which saves more energy. The proposed technologies provide approximately 57% of the number of IFFT/FFT. The use of Flip-FBMC technology consumes less energy than traditional technologies with better bit error rate (BER) performance.